POTENSI AKTIVITAS ANTIOKSIDAN DAN PENETAPAN KADAR FENOLIK TOTAL EKSTRAK DAUN KRATOM (Mitragyna speciosa Korth.) MENGGUNAKAN VARIASI PELARUT - Akhmad Riski; Nanang Fakhrudin; Agung Endro Nugroho; Rakhmadhan Niah; Lalu Husnul Hidayat (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2026)
Kratom (Mitragyna speciosa) is a medicinal plant native to Southeast Asia that contains a wide range of secondary metabolites. The characteristics of medicinal plant extracts are strongly influenced by the type of solvent used during the extraction process, particularly with respect to phenolic compounds that play a key role in antioxidant activity. This study aimed to evaluate the antioxidant activity and total phenolic content of Mitragyna speciosa leaf extracts obtained using solvents with different degrees of polarity. Kratom leaves were extracted with water using the decoction method, as well as with 70% and 90% ethanol using the maceration method. Total phenolic content was determined by Spectrophotometer UV–Vis employing the Folin–Ciocalteu reagent with gallic acid as the standard, while antioxidant activity was assessed based on IC₅₀ values using the DPPH assay. The results showed that the total phenolic content of the water, 70% ethanol, and 90% ethanol extracts was 81.27 ± 0.13, 93.85 ± 0.07, and 99.21 ± 0.07 mg GAE/g extract, respectively. Antioxidant activity analysis revealed IC₅₀ values of 64.71 µg/mL for the water extract (strong antioxidant), 35.52 µg/mL for the 70% ethanol extract (very strong antioxidant), and 35.12 µg/mL for the 90% ethanol extract (very strong antioxidant). Based on these findings, the 90% ethanol extract exhibited the highest total phenolic content and the most potent antioxidant activity, indicating its potential for development as a natural antioxidant source derived from kratom leaves.